Realisasi Belanja Pemerintah Sektor Kesehatan dan Pendidikan, serta Pengaruhnya terhadap IPM Kabupaten/Kota di Jawa Barat - Yuli Novitasari; Dila Hapitri (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2019)
This study aims to find out the evidence about the influence of health sector government spending and the education sector on the Human Development Index (HDI) of Districts and Cities in West Java Province. The type of data used is secondary data obtained from the realization of expenditures based on health and education functions in West Java Province. The analytical method used in this study is multiple linear regression analysis using simple least squares method (OLS). Data used is the data period of 2011-2016. The results of this analysis indicate that health sector government expenditure realization variables have a significant positive effect on the District and City Human Development Index (HDI) in West Java Province, while the results of the analysis for the realization variable of government expenditure in the education sector have no effect and are not significant to the Human Development Index (HDI) of the District and City in West Java Province. Taken together the realization variables of government spending in the health sector and education sector have a significant and significant impact on the Human Development Index (HDI) of Districts and Cities in West Java Province.